Causal model of separation anxiety disorder based on differentiation and empathy of mothers; a mediating role of parent-child relationship: Causal model of separation anxiety disorder based on differentiation and empathy of mothers with the mediating role of parent-child relationship - Fathi, Gona; Akbari, Maryam; Moradi, Omid; Abdollahi, Fardin (Journal of Clinical Physiotherapy Research, 2022)
Introduction:Separation anxiety disorder is relatively common, but has serious repercussions on a child's life, and if left untreated will lead to chronic satiety. The purpose of this research is to determine designing a causal model of separation anxiety disorder according to differentiation and mother's empathy with the mediating role of child- Parent relationship. Method: Research method was descriptive - correlation with structural equation modeling method. The statistical population was all of the Mothers with daughters with separation anxiety disorder syndrome whose child / children in one of the preschool centers in Kermanshah in the academic year 1399-99, and determined 600 people with table's Morgan and selected as sampling by ratio stratified random sampling method. The research data were collected through separation anxiety disorder Hahn, Hajinlian, Eisen, Winder & Pincus (2003), differentiation Drake and Moradi (2015), mother's empathy Baron-Cohen and Wheelwright (2004), child- Parent relationship Pianta (1994) questionnaires. Data analyzed in PLS software with structural equation modeling. Results: The results show that analysis of the paths of the model show that there is significance the direct effect of differentiation and mother's empathy on child- Parent relationship. There is significance the direct effect of child- Parent relationship on separation anxiety disorder. The direct effect of Self-Handicapping and perfectionism on academic Engagement is also significant. Conclusion: There is directly and indirectly significant effect of differentiation and mother's empathy on separation anxiety disorder. Differentiation, mother's empathy, child- Parent relationship can decrease separation anxiety disorder.